Independent risk factors for injury in pre-school children: three population-based nested case-control studies using routine primary care data - Orton, Elizabeth; Kendrick, Denise; West, Joe; Tata, Laila J. (Public Library of Science, 2012)
Background: Injuries in childhood are largely preventable yet an estimated 2,400 children die every day because of injury and violence. Despite this, the factors that contribute to injury occurrence have not been quantified at the population scale using primary care data. We used The Health Improvement Network (THIN) database to identify risk factors for thermal injury, fractures and poisoning in pre-school children in order to inform the optimal delivery of preventative strategies. Methods: We used a matched, nested case-control study design. Cases were children under 5 with a first medically recorded injury, comprising 3,649 thermal injury cases, 4,050 fracture cases and 2,193 poisoning cases, matched on general practice to 94,620 control children. Results: Younger maternal age and higher birth order increased the odds of all injuries. Children’s age of highest injury risk varied by injury type; compared with children under 1 year, thermal injuries were highest in those age 1-2 (OR = 2.43, 95%CI 2.23–2.65), poisonings in those age 2-3 (OR = 7.32, 95%CI 6.26–8.58) and fractures in those age 3-5 (OR = 3.80, 95%CI 3.42–4.23). Increasing deprivation was an important modifiable risk factor for poisonings and thermal injuries (tests for trend p#0.001) as were hazardous/harmful alcohol consumption by a household adult (OR = 1.73, 95%CI 1.26–2.38 and OR = 1.39, 95%CI 1.07–1.81 respectively) and maternal diagnosis of depression (OR = 1.45, 95%CI 1.24–1.70 and OR = 1.16, 95%CI 1.02–1.32 respectively). Fracture was not associated with these factors, however, not living in single-adult household reduced the odds of fracture (OR = 0.88, 95%CI 0.82–0.95). Conclusions: Maternal depression, hazardous/harmful adult alcohol consumption and socioeconomic deprivation represent important modifiable risk factors for thermal injury and poisoning but not fractures in preschool children. Since these risk factors can be ascertained from routine primary care records, pre-school children’s frequent visits to primary care present an opportunity to reduce injury risk by implementing effective preventative interventions from existing national guidelines.